High-Stability Broadband Wavelength-Tunable Single-Frequency Ytterbium-Doped All-Fiber Compound Ring Cavity - Bao-le Lu; Jin Kang; Xin-Yuan Qi; Xiao-Qiang Feng; Lei Hou; Man Jiang; Hao-Wei Chen; Yang Wang; Kai-Le Wang; Jin-Tao Bai (IEEE Photonics Journal, 2017)
A high-stability wavelength-tunable single-frequency (SF) ytterbium-doped all-fiber compound ring laser has been demonstrated experimentally. The compound ring cavity is composed of a fiber optical tunable filter, a high-finesse ring filter, and a loop mirror filter. Three segments of ytterbium-doped fibers are employed as the gain medium or saturable absorber, respectively. The SF operation is observed to be stable during 1 h without mode hopping. The SF fiber laser achieves a wide-band tunability from 1030 to 1090 nm with maximum output slope efficiency of 7.95%. The power instability over 2 h gives standard deviation value of 1.34%. The average linewidth is 8.8 kHz and the relaxation oscillation frequency is at 62 kHz.